Strategi Entrepreneurial Marketing Gocampus.Co.Id Dalam Memasarkan Perguruan Tinggi Swasta - Permadi Permadi (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to market private universities in Indonesia and help students in facilitating the search for university information even become the number one educational information resource in Indonesia, where the analysis used is Matrix Strategic Position and Action Evaluation (SPACE). The research method used is descriptive qualitative. The study was conducted by observation on the environmental conditions of the gocampus.com industry in general and specifically based on existing facts. Analysis method used in this research is entrepreneurial marketing analysis which include strategy: Guerilla marketing, ambush marketing, and word of mouth marketing strategy The result from SPACE matrix quadrant indicates that GoCampus position is in aggressive quadrant with score on horizontal axis of 3 and score on the vertical axis of 2.2. Strategies that GoCampus can run for expansion (growth) from the perspective of entrepreneurial marketing strategy can be applied with several types: Guerrilla marketing, word of mouth marketing, and Ambush marketing. Gocampus can implement an expansion strategy and improve on the strength of human resources (for example by increasing the expertise of human resources, making efficiency in human resources), and increasing Gocampus technology accessibility (eg accessible on smartphones, plug and play available on google play, and sponsorship of google play applications that have a large market share), so that the company's performance can improve, and Gocampus expands its business to increase market share (eg penetrate the international university market).